1988
DOI: 10.1007/bf00393062
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the partially coated reticulum and dictyosomes during endocytosis by soybean protoplasts

Abstract: Individual and serial sections were used to obtain detailed information regarding the morphology and distribution of the partially coated reticulum (PCR) and to determine its relationship with dictyosomes in endocytotically active soybean (Glycine max. (L.) Merr.) protoplasts. The results confirm and extend the description of the PCR provided by T.C. Pesacreta and W.J. Lucas (1985, Protoplasma 125, 173-184) from whole cells of selected angiosperms. The PCR of soybean protoplasts consists of a set of interconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…However, budding of MVBs from tubular, putative TGN structures is not restricted to recovery from drug treatment situations but can also be seen under physiological conditions. This is in agreement with earlier observations, that dilations of the partially coated reticulum (Pesacreta and Lucas, 1984;Hillmer et al, 1988) contain intralumenal vesicles (Tanchak et al, 1988). A recent electron tomographic analysis of the TGN (Kang et al, 2011) failed to provide evidence for the formation of MVBs, although it was speculated that the membrane fragments that arise as a result of TGN fragmentation may become precursors of MVBs.…”
Section: Vps2-dn Induces Increased Colocalization Of Tgn/ee and Mvb/lsupporting
confidence: 91%
See 1 more Smart Citation
“…However, budding of MVBs from tubular, putative TGN structures is not restricted to recovery from drug treatment situations but can also be seen under physiological conditions. This is in agreement with earlier observations, that dilations of the partially coated reticulum (Pesacreta and Lucas, 1984;Hillmer et al, 1988) contain intralumenal vesicles (Tanchak et al, 1988). A recent electron tomographic analysis of the TGN (Kang et al, 2011) failed to provide evidence for the formation of MVBs, although it was speculated that the membrane fragments that arise as a result of TGN fragmentation may become precursors of MVBs.…”
Section: Vps2-dn Induces Increased Colocalization Of Tgn/ee and Mvb/lsupporting
confidence: 91%
“…However, unlike the situation in animal cells, several studies have shown that higher plants do not have separate trans-Golgi network (TGN) and EE compartments (Dettmer et al, 2006;Lam et al, 2007;Reichardt et al, 2007;Otegui and Spitzer, 2008;Robinson et al, 2008;Toyooka et al, 2009;Viotti et al, 2010). The TGN in plants appears to be synonymous with the partially coated reticulum (Pesacreta and Lucas, 1984;Hillmer et al, 1988;Tanchak et al, 1988) and is a tubular-vesicular structure bearing clathrin-coated vesicles (CCVs) (Kang and Staehelin, 2008;Toyooka et al, 2009). The recent demonstration that plant retromer is present at the TGN rather than the MVB (Niemes et al, 2010b) is therefore in agreement with the location of this recycling coat complex to the tubular extensions of the EE in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, the Rab-F2/BP80 compartment has been identified in tobacco and Arabidopsis as an MVB (Tse et al, 2004;Otegui et al, 2006;Haas et al, 2007), which has been considered a later station on the endocytic route in plant cells (Tanchak et al, 1988;Geldner, 2004;Lam et al, 2007b) and other eukaryotes (Marcote et al, 2000;Pelham, 2002;Prescianotto-Baschong and Riezman, 2002;Geldner, 2004;Gruenberg and Stenmark, 2004). The Rab-F2 subclass is also involved in sorting vacuolar cargo from the Golgi, while the Rab-F2 compartment accumulates vacuolar sorting receptors and vacuolar GFP markers en route to the vacuole (Sohn et al, 2003;Kotzer et al, 2004;Zheng et al, 2005;Samalova et al, 2006), so the endocytic and vacuolar pathways may converge at the Rab-F2/BP80 compartment (Lam et al, 2007b).…”
Section: A Model For the Endosomal System In The Arabidopsis Root Tipsupporting
confidence: 53%
“…Therefore, they are very similar to an organelle previously termed the PCR (Pesacreta and Lucas, 1985). Tracer uptake studies have shown that this organelle lies on the endocytic pathway (Tanchak et al, 1988), and its relationship to the TGN has also been demonstrated (Hillmer et al, 1988). However, in our experience, the PCR as an entity lying separately and distant from Golgi stacks is rarely if ever seen in tobacco BY-2 cells.…”
Section: Scamp1-labeled Early Endosomes In Tobacco By-2 Cells Are Equmentioning
confidence: 81%